Sharing Sweet Secrets Mark Morris, Mozart and more. - Jowitt, Deborah 1934- (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Review of Mark Morris Dance Group premieres Mozart Dances. PALABRAS CLAVE: Mark Morris, Amadeus Mozart, Mozart Dance, Morris's company.